Sarcomere ACTC1 and MYO18A serum expression levels detect acute cellular rejection in cardiac transplant patients. (14th October 2021) - Perez Carrillo, L; Trivino, J C; Sanchez Lazaro, I; Martinez Dolz, L; Portoles, M; Tarazon, E; Rosello-Lleti, E
Abstract: Introduction and purpose: The development of non-invasive approaches for the early diagnosis of cardiac allograft rejection is necessary. Given the central role of sarcomeric dysfunction in cardiomyocyte biology and sarcomere alterations, described in endomyocardial biopsies of transplant patients with rejection, we hypothesized that the serum expression levels of genes encoding sarcomeric proteins were altered in acute cellular rejection (ACR). Methods: Forty consecutive serum samples from transplant recipients undergoing routine endomyocardial biopsies were included in an RNA sequencing analysis. Results: We identified 61 sarcomeric genes, 19 of which were differentially expressed in patients with clinically relevant rejection (ACR grade ≥2R). A receiver operating characteristic curve was done to assess their accuracy for ACR detection, and found that 8 relevant actins, myosins, and other sarcomere-related genes showed great diagnostic capacity (AUC≥0.800); ACTC1 (AUC=1.000, p<0.0001) and MYO18A (AUC=1.000, p<0.0001) showed the best results. MYO18A had a good ability to detect mild rejection (AUC=0.789, p<0.05). We found a relationship between MYO18A and the left ventricular end-systolic (p<0.01) and end-diastolic (p<0.05) diameters. Conclusions: ACTC1 and MYO18A also showed a significant correlation with the NT-proBNP levels (p<0.05). Because of their precision to detect ACR, we propose sarcomere ACTC1 and MYO18A serum expression levels as potential candidates for non-invasive ACR detection. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Carlos IIIEuropean Regional Development Fund (ERDF)